2020
DOI: 10.21203/rs.3.rs-25381/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GWAS unveils features between early- and late-flowering pearl millets

Abstract: Background: Pearl millet, a nutritious food for around 100 million people in Africa and India, displays extensive genetic diversity and a high degree of admixture with wild relatives. Two major morphotypes can be distinguished in Senegal: early-flowering Souna and late-flowering Sanio. Phenotypic variabilities related to flowering time play an important role in the adaptation of pearl millet to climate variability. A better understanding of the genetic makeup of these variabilities would make it possible to br… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Short cycle landraces had longer and heavier panicles compared to long cycle landraces, which had longer stems and shorter panicles. This finding was consistent with those of previous studies (Marchais, 1982;Dancette, 1983;Zongo et al, 1988;Akanvou et al, 2012;Diack et al, 2020) and was in accordance with the farmer's uses.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Short cycle landraces had longer and heavier panicles compared to long cycle landraces, which had longer stems and shorter panicles. This finding was consistent with those of previous studies (Marchais, 1982;Dancette, 1983;Zongo et al, 1988;Akanvou et al, 2012;Diack et al, 2020) and was in accordance with the farmer's uses.…”
Section: Discussionsupporting
confidence: 93%
“…GWAS analysis was thus able to highlight other phenotypic traits and notably to detect a number of polymorphisms and genes associated with yield (Supplementary Tables 5, 6). Noteworthy, our combination of approaches appears to have been effective and relevant since we were able to detect genes that had been identified in previous studies with different samples and spatial scales [five genes identified by Diack et al (2020) and Rhoné et al (2020)], suggesting false discoveries were reduced and that our results could be mainstreamed to other pearl millet landraces.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Although parts of the biosynthesis pathways regulating floral development have been verified to be relatively conserved across model plants (Litt and Kramer, 2010;Ruiz-Sola and Rodriguez-Concepcion, 2012;Saito et al, 2013), several studies on non-model plant species are needed to verify and investigate the multitude of functional alleles related to flowering time, floral shapes, pigmentation and petal numbers based on GWAS. For example, an SNP in the PPR gene was linked to flowering time leading to early-and late-flowering pearl millets (Diack et al, 2020). In another example, both known and novel genes associated with petal size were identified in rapeseed (Qian et al, 2021).…”
Section: Introductionmentioning
confidence: 99%